Synthesis and In-vitro Phosphodiesterase 5 and 5A Inhibitory Activity of Novel 3-(3-thioxo-3h-1,2-dithiol-5-yl)phenyl4-[(1e)-3-oxo-3-phenylprop-1-en-1yl]benzoate and their Analogues - Bhatia, Manish S.; Sherikar, Amol S.; Dhavale, Rakesh P. (Current Enzyme Inhibition, 2018)
Introduction: 3-(3-thioxo-3H-1,2-dithiol-5-yl)phenyl 4-[(1E)-3-oxo-3-phenylprop-1-en-1- yl]benzoate and their analogues were synthesized on the basis of Claisen-Schmidt condensation reaction wherein chalcone intermediates were synthesized by the reaction of substituted aldehydes and acetophenones. Final products were synthesized by reacting chalcone intermediates with 5-(4- hydroxyphenyl)-3H-1,2-dithiole-3-thione. Conclusion: The compounds were characterized by IR, 1H NMR, 13C NMR and elemental analysis. In in-vitro Phosphodiesterase 5 inhibitory activity, compounds G4 and G8 exhibited a significant inhibitory effect against human platelet Phosphodiesterase 5 (PDE 5) while compound G3 exhibited a significant inhibitory effect on both human platelet PDE 5 and bovine recombinant Phosphodiesterase 5A (PDE 5A). This work will be highly fruitful to design novel compounds for dealing with problems associated with vasculature.
Keywords: claisen-schmidt